The use of nuclear magnetic resonance in study of structurally dynamic membrane proteins - Phillips, Margaret (2016)
Nuclear Magnetic Resonance (NMR) spectroscopy is a powerful tool used to study both the structure and dynamics of proteins. NMR can be used for studying both crystal-like and intrinsically disordered proteins. However, for a large class of partially structured or flexible and dynamic proteins, the methodological problems such as in-homogeneous resonance line broadening which results in partial or complete loss of signal to background noise, may appear insurmountable. These partially structured proteins form a large portion of the eukaryotic proteome and play crucial roles in many important cellular processes. For my Ph.D. thesis, with the help of several NMR methods and cost-effective sample preparation, we explored the structure and dynamics of such proteins belonging to the essential class of adaptor coil-coiled proteins and membrane proteins. These proteins are either part of a dynamic complex or themselves form tetrameric channels. In particular our focus was on the following proteins: human Stromal Interaction Molecule 1 (hSTIM1), human Presenilin Enhancer-2 (hPEN-2) and E.coli water channel Aquaporin Z (AqpZ).